Proteolytic activity, degradation, and dissolution of primary and permanent teeth - Salles Scheffel, Debora Lopes [UNESP]; Cury, Jaime Aparecido; Andalo Tenuta, Livia Maria; Scheffel, Regis Henke; Perez, Cristina; Soares, Diana Gabriela [UNESP]; Basso, Fernanda Goncalves [UNESP]; Souza Costa, Carlos Alberto de [UNESP]; Pashley, David Henry; Hebling, Josimeri [UNESP] (Wiley-Blackwell, 2020)
Background Primary and permanent teeth composition may influence dissolution and degradation rates. Aim To compare the dissolution and degradation of primary and permanent teeth. Design Enamel and dentin powders were obtained from primary molars and premolars and incubated within different pH buffers. Calcium and inorganic phosphate release was quantified in the buffers by atomic absorption and light spectrophotometry. A colorimetric assay was used to assess the MMP activity of primary dentin (PrD) and permanent dentin (PeD). Collagen degradation was assessed by dry mass loss, change in elastic modulus (E), and ICTP and CTX release. Data were submitted to ANOVA and Tukey's tests (alpha = 0.05). Results Similar dissolution was found between PrD and PeD after 256 hours. At pH 4.5, enamel released more minerals than dentin whereas at pH 5.5 the inverse result was observed. MMP activity was similar for both substrates. PrD showed higher dry mass loss after 1 week. In general, greater reduction inEwas recorded for PrD. Higher quantities of ICTP and CTX were released from PrD after 1 week. Conclusions Primary and permanent teeth presented similar demineralization rates. Collagen degradation, however, was faster and more substantial for PrD.
Keywords: collagen; dentin; dissolution; enamel; proteases